Effects of Continuous Irrigation During Burring on Thermal Necrosis and Fusion Strength in a Rabbit Arthrodesis Model. (August 2014) - Haddad, Steven L.; Hsu, Andrew R.; Templin, Cary R.; Ren, Yupeng; Stewart, Bruce; Kohli, Navjot S.; Zhang, Li-Qun
Background: High-speed burring used to prepare bony surfaces during arthrodesis procedures can increase heat generation that may impede healing and fusion. Irrigation during burring has the potential to improve early healing of burred bone surfaces and result in a stronger fusion mass. The purpose of this study was to determine the effects of continuous irrigation during burring on thermal necrosis and fusion strength in an in vivo arthrodesis animal model. Methods: A small joint rabbit ulnohumeral arthrodesis model was developed and utilized in 16 New Zealand white rabbits. Joints were prepared and contoured using a high-speed cutting burr and fixed in compression with crossed screws to obtain fusion. Prepared bony surfaces were either irrigated (n = 8) with chilled 6°C (43°F) saline or not irrigated (n = 8). Specimens were harvested, radiographed, mechanically tested for torque to failure and stiffness, and evaluated for histology. Results: Fusion rate was 100% (8/8) when joints were irrigated during burring and 75% (6/8) when joints were not irrigated ( P = .45). Mechanical testing showed a mean torque to failure of 0.85 Nm and 0.72 Nm in irrigated and nonirrigated specimens, respectively ( P = .57). Histology showed evidence of less mature osseous formation in nonirrigated specimens compared to irrigated specimens. Conclusion: There was an overall trend toward decreased fusion rate and lower fusion mass strength in nonirrigated fusion specimens compared with those treated with chilled irrigation during bone preparation. Clinical Relevance: Continuous chilled irrigation during bone preparation with burring may have a positive effect on fusion rate and fusion mass strength for arthrodesis procedures.